Ancient Angkor - Freeman, Michael 1945-; Jacques, Claude (Bangkok River Books, 1999)
Guide to art and architecture of Angkor, extinct city, Cambodia.
History -- Religion -- Khmer temples -- Daily life -- Inscriptions -- Discovery & restoration -- Central Angkor -- Eastern Angkor -- The East Baray -- Banteay Srei.
Keywords: Temples -- Cambodia -- Angkor (Extinct city); Architecture, Khmer -- Cambodia -- Angkor (Extinct city); Angkor (Extinct city).; Angkor (Extinct city) -- Pictorial works; Cambodia -- Antiquities; Angkor (Extinct city) -- Buildings, structures, etc